2009
DOI: 10.1007/s00497-009-0123-2
|View full text |Cite
|
Sign up to set email alerts
|

Sperm dimorphism in terms of nuclear shape and microtubule accumulation in Cyrtanthus mackenii

Abstract: Pollen tubes of Cyrtanthus mackenii, a species with bicellular pollen, were cultured in vitro to investigate nuclear phase changes during generative cell division and male germ unit (MGU) formation using flow cytometric analysis. Results revealed that sperm cells were formed after 12 h of culture. During sperm maturation, the nuclei of sperm cells were not associated with the vegetative nucleus (unassociated sperm cells; Sua) and became longer than those of sperm cells associated with the vegetative nucleus (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Sperm formation in C. mackenii begins at 9–12 h of culture (Hirano and Hoshino 2010 a ). For a detailed analysis of sperm cell formation, we investigated the cell cycle phase in PMII of irradiated pollen grains after 12 h of culture by isolating male gametes from the pollen tubes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sperm formation in C. mackenii begins at 9–12 h of culture (Hirano and Hoshino 2010 a ). For a detailed analysis of sperm cell formation, we investigated the cell cycle phase in PMII of irradiated pollen grains after 12 h of culture by isolating male gametes from the pollen tubes.…”
Section: Resultsmentioning
confidence: 99%
“…To observe the cell cycle phase in PMII and the distribution of phosphorylated histone H2AX (γH2AX) in the generative cells and sperm cells, immunofluorescence analysis was performed according to the methods described by Hirano and Hoshino (2010 a ) with several modifications. After 12 or 24 h of culture the generative cells or sperm cells in the pollen tubes were isolated and simultaneously fixed for 30 min in fixative containing 4 % (w/v) paraformaldehyde, 0.1 % (v/v) glutaraldehyde and 2 % (v/v) polyoxyethylene (20) sorbitan monolaurate in microtubule-stabilizing buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heteromorphic sperm also occur in angiosperms (e.g. Saito et al, 2002;Weterings & Russell, 2004;Gou et al, 2009;Hirano & Hoshino, 2010). Heteromorphic pollen in angiosperms, and sperm in animals have been suggested to be convergent, having both evolved via sexual selection to increase male success (Till-Bottraud et al, 2005).…”
Section: Sperm Variationmentioning
confidence: 99%
“…Further, female partners of infected men with spermatozoa in their ejaculate had a significantly higher incidence of upper genital tract infection compared to infected men who have been vasectomised (Toth et al, 1984). Interestingly it was recently reported that a significantly higher incidence of sperm-immobilizing antibodies (6.4%) was found in sera collected from 273 infertile women with a past C. trachomatis infection compared to that found in women without a past chlamydial infection (1.5%) (Hirano & Hoshino 2010). Thus, it may be that the production of sperm-immobilizing antibodies in infertile women is the result of a past C. trachomatis infection in these women and this may contribute to their infertility.…”
Section: Upper Genital Tract Infectionsmentioning
confidence: 93%